A proof-of-concept randomized controlled trial of follow-up mental health care for traumatic injury patients following hospital discharge. Issue 5 (May 2023) - Joseph, Anthony P; Wallman, Matthew; Scott, Elliot; Ilchef, Ralf; Harris, Newman; Jackson, Alicia; Bryant, Richard A.
Highlights: Although traumatic injury patients often experience psychological difficulties, many do not seek mental health assistance. In a controlled trial, patients who were monitored after discharge and referred for specialist help had less disability than usual care. Regular monitoring of traumatic injury patients for psychological status after hospital discharge may lead to better outcomes. Abstract: Introduction: Traumatic injuries account for a huge burden of disease. Many patients develop persistent mental health problems in the months following hospital discharge. This proof-of-concept trial investigated whether Stepped Care comprising follow-up assessment telephone calls and appropriate referral information would lead to better mental health and functioning in traumatic injury patients. Methods: Patients admitted to the Trauma Service at Royal North Shore Hospital were randomized to either Stepped Care ( n = 84) or Treatment as Usual ( n = 90). All patients were assessed for anxiety, depression, and posttraumatic stress prior to hospital discharge. Those in Stepped Care received a telephone call at 1-month and 3-months after hospital discharge in which they were administered a brief assessment; patients who reported mental health or pain difficulties were provided with information for local specialists to address their specific problem. All patients were independently assessed by telephone interview 9- months after hospital discharge for posttraumatic stress disorder (PTSD) (primary outcome), as well as for anxiety, depression, disability, and pain. Results: There were 58 (73%) patients that could be contacted at either the 1-month or 3-month assessments. Of those contacted, 28 patients (48% of those contacted) were referred for specialist assistance. There were no differences between treatment arms on PTSD symptoms at follow-up [ F 1, 95 = 0.55, p = 0.46]. At the 9-month assessment, patients in the Stepped Care condition reported significantly less anxiety [ F 1, 95 = 5.07, p = 0.03] and disability [ F 1, 95 = 4.37, p = 0.04] relative to those in Treatment as Usual. At 9 months there was no difference between conditions on depression [ F 1, 95 = 1.03, p = 0.31]. There were no differences between conditions on self-reported pain difficulties. Conclusions: This proof-of-concept trial suggests that brief screening assessments of traumatic injury patients following hospital discharge, combined with appropriate referral information, may lead to better functional outcomes. Further research is needed with larger sample sizes and greater verification of referral uptake to validate this finding.